THE EFFECT OF SOCIAL MEDIA MARKETING ON CONSUMER PURCHASE INTENTION IN MSMEs IN TANJUNG SARI SUBDISTRICT - Kristine; Mila Yulia Herosian; Velix Sun; Dwita Sakuntala (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to analyze the effect of social media marketing on consumer purchase intention through consumer interaction in SMEs (Small and Medium Enterprises) in Tanjung Sari Village, Medan Selayang District, Medan City. The research approach used is quantitative with a causal associative method, where social media marketing is the independent variable, consumer purchase intention is the dependent variable, and consumer interaction is the mediating variable. Data were collected through the distribution of questionnaires to 57 respondents who were involved in interaction and purchase of products from SMEs in Tanjung Sari Village. The analysis results using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) indicate that social media marketing has a positive and significant effect on consumer purchase intention and increases consumer interaction with SME products. In addition, consumer interaction was also found to mediate the effect of social media marketing on consumer purchase intention. These findings suggest that SMEs need to improve the management of social media marketing and increase interaction with consumers to drive greater purchase intention and strengthen consumer relationships.